Informal education management to reduce the inequality in the knowledge dimension by Surat Thani City Community Parents Network - Thongkaew, Krishna; บุญกำเนิด, เสน่ห์ (RMUTL Journal of Socially Engaged Scholarship, 2024)
This research aimed to 1) investigate the potential of the parent network in informal education in the Surat Thani community, 2) develop informal education to increase life skills among children and youth through the parent network, and 3) drive informal education policy in the Surat Thani community. The findings revealed that the parent network was developed among 20 urban families with parents who worked in business, government, and agriculture. There were 31 young people enrolled in informal education. It was found that parents who were businessmen concentrated on online media literacy, social etiquette, social capital, and the city's potential. Parents who were government officials concentrated on expert knowledge, online media literacy, social etiquette, the capital and city's potential, kinship, and social groups, respectively. Parents who were farmers concentrated on kinship, social group, online media literacy, social etiquette, the city's potential, and expert knowledge, respectively. In conclusion, the network of urban parents influenced the reduction of knowledge inequality among their children. As a result, a discussion activity for the urban parent network to continually share knowledge should be developed. To ensure proper learning outcomes in the twenty-first century, an informal education network should be formed by allowing a network of urban parents to engage in planning, producing, assessing, and overseeing informal education.